1999
DOI: 10.1002/1529-0131(199907)42:7<1322::aid-anr4>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, safety, and efficacy of combination treatment with methotrexate and leflunomide in patients with active rheumatoid arthritis

Abstract: Objective. To examine the safety and pharmacokinetics of and clinical response to leflunomide, a de novo pyrimidine synthesis inhibitor, when administered to patients with active rheumatoid arthritis (RA) who have been receiving long-term methotrexate therapy.Methods. This was an open-label, 52-week study in which 30 patients with RA that remained active despite therapy with methotrexate at 17 ؎ 4 mg/week (mean ؎ SD) for >6 months were given leflunomide, 10-20 mg/day. Patients were assessed for adverse effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
0
17

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 242 publications
(122 citation statements)
references
References 16 publications
5
100
0
17
Order By: Relevance
“…Efficacy ranging from 50 to 87% with monotherapy using various assessment criteria, have been observed in studies in different situations to date, irrespective of the absence of the loading dose. [5][6][7][11][12][13][14][15][16][17] Hematological and biochemical parameters showed no significant change. Few patients had liver enzyme elevation, though it did not reach significance and only one had to discontinue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Efficacy ranging from 50 to 87% with monotherapy using various assessment criteria, have been observed in studies in different situations to date, irrespective of the absence of the loading dose. [5][6][7][11][12][13][14][15][16][17] Hematological and biochemical parameters showed no significant change. Few patients had liver enzyme elevation, though it did not reach significance and only one had to discontinue.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown liver enzyme elevation, which subsequently normalized. [6,7,[15][16][17] Twenty four (29%) patients dropped out of the study and an adverse event was observed in 15 patients, of which five withdrew. Skin reactions observed were more of type B adverse event, which were unpredictable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combinations of infliximab, etanercept, or leflunomide with MTX have all been studied in patients who had a partial response to MTX, and the combinations were found to be beneficial (93,94,(130)(131)(132).…”
Section: Pharmacologic Treatment Of Ramentioning
confidence: 99%
“…A recent international multicenter study demonstrated that ϳ60% of 1,399 patients with rheumatoid arthritis (RA) take a mean glucocorticoid dosage of 6.6 mg/day of prednisone equivalent (12). This figure appears to be even higher in the US, reaching ϳ70%, whereas the corresponding figure for Europe is lower (only ϳ25%) when taken from recent clinical trials (13)(14)(15). However, glucocorticoid use in routine practice might differ from use in clinical trials because trial participants do not represent the full patient spectrum.…”
Section: Introductionmentioning
confidence: 99%